ROLE OF ALUMINIUM IN THE SILICATE NETWORK: IN SITU, HIGH-TEMPERATURE STUDY OF GLASSES AND MELTS ON THE JOIN SIO2-NAALO2 - Neuville D.R.; Mysen B.O. (My University, 1996)
The structure of glasses and melts in the NaAlSiO2-SiO2 system was determined in situ as a function of temperature by Raman spectroscopy, in the temperature range of 300 K–1800 K. The high-frequency envelope of the Raman spectra of Al-free SiO2 glass is deconvoluted in three different bands (1050, 1150, and 1200 cm−1) with the 1150 and 1200 cm−1 bands attributed to Si-O0 stretch vibrations in Q4 species in the fully polymerized network. There is a decrease in their frequencies with increasing Al/(Al + Si) of the glasses and melts in the Al/(A1 + Si) range investigated (0–0.5).The spectra are consistent with Al3+Si4+ substitution in two coexisting, three-dimensionally interconnected structural units. These units have different average intertetrahedral angles. Aluminum partitions preferentially into the unit with the smaller angle at low Al/(Al + Si) (less than ~0.3), and into the unit with the larger angle at higher concentrations. There is no evidence for major structural changes (i.e., redistribution of Al) in the glasses and melts as a function of increasing temperature.